Digital Media Economies and the Neoliberal Colonialism of the Visual Field. - OCCHIETTI, RAPHAELLE (Afterimage, 2023)
The article explores the intersection of globalization, migration, and the archive in the context of cinematic heritage and media piracy in Pakistan. Topics include the challenges faced by Pakistan in constructing its cinematic archive, the impact of media piracy on cultural heritage, and the role of neoliberalism in shaping contemporary media economies.